1994
DOI: 10.1210/jcem.79.5.7962330
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol production by granulosa cells of normal and polycystic ovaries: relationship to menstrual cycle history and concentrations of gonadotropins and sex steroids in follicular fluid.

Abstract: The underlying cause of anovulation in polycystic ovary syndrome is unknown. Circulating levels of immuno- and bioactive FSH are within the normal range, and the follicles contain measurable levels of bioactive FSH. The aim of this study was to compare estradiol (E2) production in response to FSH by granulosa cells from normal ovaries with those from polycystic ovaries derived from both anovulatory (anovPCO) and ovulatory subjects (ovPCO). Intrafollicular levels of immunoactive FSH, E2, and androstenedione in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
44
1
3

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 3 publications
15
44
1
3
Order By: Relevance
“…The implication of these findings is that granulosa cells from insulinresistant women with PCOS are, effectively, exposed to higher than normal circulating concentrations of insulin and that this may be expected to enhance steroidogenesis. This would be consistent with the observation that granulosa cells from anovulatory PCOS subjects have a greater capacity to produce oestradiol in vitro than do cells from either normal ovaries or ovulatory PCOS (Mason et al, 1994). How can this proposed stimulatory effect of insulin be reconciled with the observation that PCOS is associated with disordered follicle maturation?…”
Section: Menstrual Function and Insulinsupporting
confidence: 77%
See 1 more Smart Citation
“…The implication of these findings is that granulosa cells from insulinresistant women with PCOS are, effectively, exposed to higher than normal circulating concentrations of insulin and that this may be expected to enhance steroidogenesis. This would be consistent with the observation that granulosa cells from anovulatory PCOS subjects have a greater capacity to produce oestradiol in vitro than do cells from either normal ovaries or ovulatory PCOS (Mason et al, 1994). How can this proposed stimulatory effect of insulin be reconciled with the observation that PCOS is associated with disordered follicle maturation?…”
Section: Menstrual Function and Insulinsupporting
confidence: 77%
“…5-10 mm in diameter) may be effectively equivalent to that which, in the normal menstrual cycle, is attained only in mature follicles of about 20 mm in diameter. The predicted result would be enhanced oestradiol production (as indeed can be observed in studies in vitro, Mason et al, 1994) but inhibition of further growth and arrest of follicles at 5-10 mm (Fig. 6).…”
Section: Menstrual Function and Insulinsupporting
confidence: 59%
“…Since serum FSH concentrations are normal in PCOS patients and granulosa cells respond in a normal fashion to stimulation in vitro with FSH [27], local ovarian products might be involved in the follicular arrest characteristic of PCOS. In a recent report by Welt et al [28], decreased concentrations of inhibin A and B were found in follicular fluid samples from PCOS patients as compared to concentrations in size-matched follicles obtained from healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical studies of polycystic ovaries could not detect aromatase in antral follicles of various sizes (53). On the other hand it has been found that granulosa cells from anovulatory polycystic ovaries are hyperresponsive to follicle-stimulating hormone (FSH) in vitro, displaying significantly greater oestradiol production than granulosa cells from normal ovaries, suggesting no functional deficiency of aromatase in polycystic ovaries (54).…”
Section: The Aromatase Gene (Cyp19)mentioning
confidence: 99%